Ascochyta blight in North Dakota field pea: the pathogen complex and its fungicide sensitivity - Fonseka, Dimitri L.; Markell, Samuel G.; Zaccaron, Marcio L.; Ebert, Malaika K.; Pasche, Julie S. (Frontiers in Plant Science, 2023)
Worldwide, Ascochyta blight is caused by a complex of host-specific fungal pathogens, including Ascochyta pisi, Didymella pinodes, and Didymella pinodella. The application of foliar fungicides is often necessary for disease management, but a better understanding of pathogen prevalence, aggressiveness, and fungicide sensitivity is needed to optimize control. Leaf and stem samples were obtained from 56 field pea production fields in 14 counties in North Dakota from 2017 to 2020 and isolates were collected from lesions characteristic of Ascochyta blight. Based on fungal characteristics and sequencing the ITS1-5.8S-ITS2 region, 73% of isolates were confirmed to be D. pinodes (n = 177) and 27% were A. pisi (n = 65). Across pathogens, aggressiveness was similar among some isolates in greenhouse assays. The in vitro sensitivity of all D. pinodes isolates collected from 2017 to 2020 was lower than that of the three baseline isolates. Sensitivity of 91% of A. pisi isolates collected in 2019 and 2020 was lower than the sensitivity of two known sensitive isolates. Resistance factors (Rf) from mean EC50 values of pyraclostrobin baseline/ known sensitive isolates to isolates collected from 2017 to 2020 ranged from 2 to 1,429 for D. pinodes and 1 to 209 for A. pisi. In vitro prothioconazole sensitivity of 91% of D. pinodes isolates collected from 2017 to 2020 was lower than the sensitivity of the baseline isolates and 98% of A. pisi isolates collected from 2019 to 2020 was lower than the sensitivity of the known sensitive isolates. Prothioconazole Rf ranged from 1 to 338 for D. pinodes and 1 to 127 for A. pisi. Based on in vitro results, 92% of D. pinodes and 98% of A. pisi isolates collected displayed reduced-sensitivity/ resistance to both fungicides when compared to baseline/ known sensitive isolates. Disease control under greenhouse conditions of both pathogens provided by both fungicides was significantly lower in isolates determined to be reduced-sensitive or resistant in in vitro assays when compared to sensitive. Results reported here reinforce growers desperate need of alternative fungicides and/or management tools to fight Ascochyta blight in North Dakota and neighboring regions.